Pemahaman Konsep Matematika Melalui Pendidikan Progresif dengan Penggunaan Kalkulator Saintifik - Kiki Rizki Amalia (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The current education system must change according to the times. The existing conventional education system makes students far behind in keeping up with the times. Students are asked to remember knowledge from authentic sources such as reading textbooks, parents who rarely take part in educating their children, knowledge is only obtained from the results of teacher conversations in class, based on assignments given, very rare mastery of skills, and in the assessment, process are boxed according to the highest and lowest ratings. This conventional education system makes school a mandatory task and students must find ways to overcome it. The understanding of students' concepts is very lacking, especially the specter of mathematics which is seen as a difficult and long calculation. Progressive education is here to replace the current conventional education system and the use of scientific calculator digital technology media greatly facilitates students in understanding mathematical concepts which will be achieved from the indicators of concept understanding as follows: 1) restating the concepts that have been studied, (2) classifying objects -objects to achieve the formation of a concept, (3) identify the properties of a concept, (4) apply the concept logically, (5) provide correct and incorrect examples/contras of the concept being studied, (6) present the concept in the form of various kinds of mathematical representations such as tables, graphs, diagrams, pictures, sketches, or other mathematical models, (7) linking various concepts in mathematics and outside mathematics, (8) developing the requirements needed in understanding concepts.